Methods for assessing the performance of internal audit - Badea, Georgiana; Spineanu-Georgescu, Luciana (Annals of Spiru Haret University. Economic Series, 2016)
The positive effect / added value brought to an economic entity through internal audit function requires effective measurement criteria. It is true that it looks pretty difficult to establish this kind of values (the value added by internal audit in the enterprise). Touching internal audit performance involves, as in any other activity, the existence of resources (financial, material, human) and effective and efficient combination of them. It is important that these resources be properly budgeted and allocated where needed, depending on the moment. Thus, this paper seeks to identify ways of assessing internal audit and to determine performance of internal audit mission based on specific indicators.